Pengaruh Brand Love Terhadap Purchase Intention Melalui Brand Jealousy - Shafa' Annisa Puspasari; Arief Noviarakhman Zagladi (Komunitas Dosen Indonesia, 2024)
The consumption of luxury goods in the world is currently increasing. However, for some people, purchasing luxury branded goods is not only to meet basic needs, but also to show their exclusivity and social class in front of the public. The purpose of this study was to determine the factors that can influence purchasing interest such as brand love and brand jealousy. This study uses a quantitative method with descriptive and explanatory research types. To determine this influence, a survey was conducted using a questionnaire distributed to 100 respondents. The data analysis technique was carried out using Partial Least Square (PLS) using SmartPLS software. The results of the study showed that brand love has a direct and indirect effect on purchasing interest mediated by brand jealousy. Brand love was also found to have a positive effect on brand jealousy. In addition, brand jealousy also has a positive effect on purchase intention.